Enhanced Biomass Properties In Sludge Bulking: Impact of Static Magnetic Field. Issue 1 (September 2020) - Syamimi Zaidi, Nur; Sohaili, Johan; Hussein, Norelyza; Burhanuddin Bahrodin, Muhammad
Abstract: Occurrence of sludge bulking with regard to prolong sludge age declines the removal performances attributable to the failure of aggregation by the floc-formers and insufficient adhesion among cells' surfaces. Approach of sufficiently minimizing the sludge age had been taken most of the times. This approach, however, eliminated the floc-formers although it was found to inhibit the bulking. The aim of the present study, therefore, is to investigate the potential of magnetic field application as an alternative approach to control the sludge bulking. Two sequencing batch reactors, Reactor A (SBRA ) and Reactor B (SBRB ), were operated in long sludge age to induce the bulking. SBRA was subjected to 88.0 mT magnetic field intensity while SBRB served as a control system. The findings showed that the magnetic field was able to enhance the biomass properties including the aggregation ability, relative hydrophobicity and maintain significant negative surface charge under an adverse effect of long sludge age thus led to more stable flocs been formed. This had resulted with consistent high removal of SBRA compared to SBRB . Consequently, this approach minimizes the occurrence of sludge bulking.